2006
DOI: 10.1111/j.1744-7429.2006.00240.x
|View full text |Cite
|
Sign up to set email alerts
|

Bat Diversity and Movement in an Agricultural Landscape in Matiguás, Nicaragua

Abstract: Although agriculture dominates much of Central America, little is known about the bat assemblages that occur within agricultural landscapes and how bats use different types of tree cover within these landscapes. Using mist‐nets and a mark‐recapture protocol, we compared bat diversity and movement across six types of tree cover within an agricultural landscape in central Nicaragua. The tree cover types surveyed included secondary forests, riparian forests, forest fallows, live fences, pastures with high tree co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
84
1
20

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(107 citation statements)
references
References 33 publications
2
84
1
20
Order By: Relevance
“…Atribuimos estos resultados a la preferencia de estas especies por bosques continuos y a la baja movilidad y ámbitos de acción pequeños (<9ha) (Fenton et al 2001;Albrecht et al 2007;Chaverri et al 2007;Medina et al 2007). Por otro lado, los murciélagos de tamaño grande como A. lituratus y Vampyrodes major son afectados por la densidad y tamaño de los fragmentos.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Atribuimos estos resultados a la preferencia de estas especies por bosques continuos y a la baja movilidad y ámbitos de acción pequeños (<9ha) (Fenton et al 2001;Albrecht et al 2007;Chaverri et al 2007;Medina et al 2007). Por otro lado, los murciélagos de tamaño grande como A. lituratus y Vampyrodes major son afectados por la densidad y tamaño de los fragmentos.…”
Section: Discussionunclassified
“…Se ha observado que estos murciélagos poseen alta movilidad y explotan una serie de recursos (Ficus spp.) en todo el paisaje fragmentado (Morrison 1980;Handley et al 1991;Estrada & Coates-Estrada 2002;Medina et al 2007), y la configuración del paisaje podría no ser un elemento determinante como lo es la composición (Meyer & Kalko 2008).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…For example, more than a decade of research in a rural landscape in Coto Brus, Costa Rica has documented the area's substantialalbeit modified-assemblage of native biodiversity (Daily and Ehrlich 1995, 2003, Hughes et al 2002, Horner-Devine et al 2003, Luck and Daily 2003, Mayfield and Daily 2005, Lindell et al 2006, Ranganathan et al 2007, Sekercioglu et al 2007). Other research hotspots have included coffee agroecosystems in Chiapas, Mexico (Perfecto et al 2003), mosaics of lowland rainforest and various cropping systems in Los Tuxtlas, Veracruz, Mexico (Estrada et al 1993, 1994, 1997, 2000, Estrada and CoatesEstrada 2001, 2002, cacao agroforests and competing land uses in Talamanca, Costa Rica (Reitsma et al 2001, Suatunce et al 2003, Harvey et al 2006a, and several pasture-dominated landscapes in Costa Rica and Nicaragua (Harvey et al 2005, Harvey et al 2006b, Pérez et al 2006, Medina et al 2007). This collective body of research has provided important evidence on the contributions and limitations of wildlifefriendly farming as a conservation strategy in Central America.…”
Section: Introductionmentioning
confidence: 99%
“…A hypothesis based only on D. rotundus displacement patterns cannot explain this genetic similarity because, according to studies on hematophagous bat biology, the maximum distance they are able to cover is 20 km (GREENHALL; SCHMIDT, 1988;CRESPO et al, 1961;MEDINA et al, 2007), and distances observed in this study are superior to their radius of movement.…”
Section: Discussionmentioning
confidence: 68%